The Issue of the Didactic Aspect of the Activity of Play - Tasevska, Alma (EUSER, 2017)
The application of the activity of play for educational purposes has caused heated debates among the scientific audience. The content of the didactic games is mainly determined by the program, thus it takes up the shape of a task that should be solved. What is of great significance are the rules that the pupils should follow in order to achieve the desired goal, which is in fact solving the task and finishing the game. In every didactic game, there is the expected result, which on the one hand carries the feeling of satisfaction from the achieved success, while on the other hand, represents a marker of the degree of development. In the orientation of the didactic games, two extremes can be differentiated: The child’s development is left fully to the children’s spontaneous activities, which are most often the children’s self-created games; Didactization of games – its complete transformation and inclination towards strictly directed and previously established educational goals. Hence, the question posed regards whether the activity of game can be freed from its didactic aspect or whether it can be interpreted more freely, in the holistic spirit of contemporary pedagogy. The subject of research in this work is directed towards the didactic aspect of the activity of play. The methods and techniques that were applied are the following: the method of analysis, the inductive, descriptive and the method of generalization, as well as the techniques of analysis of pedagogical documentation, observation and surveying. On the basis of the received results, it can be concluded that: The professional readiness of the teachers is of vital importance to the organization and the realization of the activities of play; Equivalents of the teaching programs are necessary for the realization of the activity of play in the first educational cycle; There is a need for respect towards children’s interests, needs and previous knowledge as the foundation in the didactic-methodic preparation of the activity of play; There is need for creating a contemporary concept of didactic materials that shall be applied in the realization of the activity of play.
Keywords: didactic aspect, didactic games, activity of play, teaching